(untitled) (Research, Society and Development, 2021)
Cranioencephalic traumatism (TBI) is a common situation in trauma hospitals and has become responsible for high rates of mortality worldwide. When the victim of TBI is affected by injuries to the skullcap with a need for grafting, problems regarding the availability of suitable and affordable materials eventually happen. In this study, a 3D structure of Polyetheretherketone (PEEK) that mimics the cranial bone morphology for use in cranioplasty was developed. Samples of different formulations, in the form of round bars, were obtained through uniaxial compression, and porosity was controlled by the salt leaching technique. Then, the specimens were characterized in terms of pore morphology and distribution, surface roughness, compression resistance and cytotoxicity. Results exhibited high levels of similarity of the 3D strutures of PEEK to the natural human bone, which indicates the effectiveness of the proposed method in mimicking the morphology of the compact/porous/compact system of the skullcap (diploe).